Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = 1,3 + 0,7x}[/tex]
[tex]\mathsf{g(x) = 1 + 0,9x}[/tex]
[tex]\mathsf{f(150 - y) = g(150 - x)}[/tex]
[tex]\mathsf{1,3 + 0,7(150 - y) = 1 + 0,9(150-x)}[/tex]
[tex]\mathsf{1,3 + 105 - 0,7y = 1 + 135 - 0,9x}[/tex]
[tex]\mathsf{106,3 - 0,7y = 136 - 0,9x}[/tex]
[tex]\mathsf{0,9x - 0,7y = 136 - 106,3}[/tex]
[tex]\begin{cases}\mathsf{0,9x - 0,7y = 29,7}\\\mathsf{x + y = 150}\end{cases}[/tex]
[tex]\mathsf{0,7y = 29,7 - 0,9x}[/tex]
[tex]\mathsf{y = \dfrac{0,9x - 29,7}{0,7}}[/tex]
[tex]\mathsf{x + \dfrac{0,9x - 29,7}{0,7} = 150}[/tex]
[tex]\mathsf{0,7x + 0,9x - 29,7 = 105}[/tex]
[tex]\mathsf{1,6x = 134,7}[/tex]
[tex]\boxed{\boxed{\mathsf{x = 84,1875\:km}}}[/tex]